IMPLEMENTATION OF THE ANALYTICAL HIERARCHY PROCESS (AHP) METHOD IN DECISION SUPPORT SYSTEMS ASSESSMENT OF STUDENT LEARNING OUTCOMES - Jijon Raphita Sagala; Penda Sudarto Hasugian (Sean Institute, 2022)
The achievements of students at SD Negeri 0640 22 Medan are not only in the academic field, but also in non-academic achievements, attitudes, behaviors, talents, organizational history, and extracurricular achievements based on the 2013 curriculum. , where students who master a subject are often invisible because of their misbehavior, student achievement is only measured when students enter the top 10 rankings, while other students who can only master one subject are not seen as achieving because they are not included in the top 10 Rankings , because the scores of other subjects get low results, for example only mastering mathematics and English. Therefore SD Negeri 064022 Medan requires a Decision Support System to become a standard measure for assessing student learning outcomes for students' learning abilities at school, a decision support system capable of providing recommendations about outstanding students which is the result of multi-criteria processing using the Analytical Hierarchy Process method. (AHP).